Tetraoxygenated xanthones from the latex of Garcinia cowa growing in Viet Nam - Nguyen Thi Kim An; Dinh Thi Ha; Pham Quoc Long; Tran Thi Thu Thuy (Vietnam Journal of Science and Technology, 2018)
Seven tetraoxygenated xanthones, namely fuscaxanthone A,7-O-methylgarcinone E, cowagarcinone A, cowaxanthone, rubraxanthone, cowanin and cowanol, were isolated from the dichloromethane extract of the latex of Garcinia cowa_Roxb. ex Choisy. Their structures were elucidated on the basis of 1D, 2D NMR spectroscopic data and comparison with reported data.